Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find the transformation of the function [tex]\( f(x) = 3(x+2)^2 \)[/tex] to get the function [tex]\( g(x) \)[/tex] which results from a translation 1 unit left and 6 units down, followed by a vertical stretch by a factor of 2, we will follow these steps:
### Step-by-Step Solution:
1. Original Function:
[tex]\( f(x) = 3(x+2)^2 \)[/tex]
2. Translate the Function:
- Translating a function 1 unit left involves replacing [tex]\( x \)[/tex] with [tex]\( x + 1 \)[/tex].
- Translating a function 6 units down involves subtracting 6 from the function.
Applying the translation:
[tex]\[ g_{translated}(x) = f(x + 1) - 6 \][/tex]
Let's compute [tex]\( f(x + 1) \)[/tex]:
[tex]\[ f(x + 1) = 3(x + 1 + 2)^2 = 3(x + 3)^2 \][/tex]
Now subtract 6:
[tex]\[ g_{translated}(x) = 3(x + 3)^2 - 6 \][/tex]
3. Vertical Stretch:
- A vertical stretch by a factor of 2 involves multiplying the function by 2.
Applying the vertical stretch:
[tex]\[ g(x) = 2 \cdot g_{translated}(x) \][/tex]
Substitute [tex]\( g_{translated}(x) \)[/tex] into the equation:
[tex]\[ g(x) = 2 \left( 3(x + 3)^2 - 6 \right) \][/tex]
4. Simplify the Expression:
Distribute the 2:
[tex]\[ g(x) = 2 \cdot 3(x + 3)^2 - 2 \cdot 6 \][/tex]
Simplify:
[tex]\[ g(x) = 6(x + 3)^2 - 12 \][/tex]
### Final Function:
[tex]\[ g(x) = 6(x + 3)^2 - 12 \][/tex]
Thus, the function [tex]\( g(x) \)[/tex] which results from a translation 1 unit left and 6 units down, followed by a vertical stretch by a factor of 2 of the graph of [tex]\( f(x) = 3(x+2)^2 \)[/tex], is:
[tex]\[ g(x) = 6(x+3)^2 - 12 \][/tex]
### Step-by-Step Solution:
1. Original Function:
[tex]\( f(x) = 3(x+2)^2 \)[/tex]
2. Translate the Function:
- Translating a function 1 unit left involves replacing [tex]\( x \)[/tex] with [tex]\( x + 1 \)[/tex].
- Translating a function 6 units down involves subtracting 6 from the function.
Applying the translation:
[tex]\[ g_{translated}(x) = f(x + 1) - 6 \][/tex]
Let's compute [tex]\( f(x + 1) \)[/tex]:
[tex]\[ f(x + 1) = 3(x + 1 + 2)^2 = 3(x + 3)^2 \][/tex]
Now subtract 6:
[tex]\[ g_{translated}(x) = 3(x + 3)^2 - 6 \][/tex]
3. Vertical Stretch:
- A vertical stretch by a factor of 2 involves multiplying the function by 2.
Applying the vertical stretch:
[tex]\[ g(x) = 2 \cdot g_{translated}(x) \][/tex]
Substitute [tex]\( g_{translated}(x) \)[/tex] into the equation:
[tex]\[ g(x) = 2 \left( 3(x + 3)^2 - 6 \right) \][/tex]
4. Simplify the Expression:
Distribute the 2:
[tex]\[ g(x) = 2 \cdot 3(x + 3)^2 - 2 \cdot 6 \][/tex]
Simplify:
[tex]\[ g(x) = 6(x + 3)^2 - 12 \][/tex]
### Final Function:
[tex]\[ g(x) = 6(x + 3)^2 - 12 \][/tex]
Thus, the function [tex]\( g(x) \)[/tex] which results from a translation 1 unit left and 6 units down, followed by a vertical stretch by a factor of 2 of the graph of [tex]\( f(x) = 3(x+2)^2 \)[/tex], is:
[tex]\[ g(x) = 6(x+3)^2 - 12 \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.